Trust-based security routing mechanism in mobile social networks - Yang, Shuang; Wang, Xingwei; Zhang, Shuang; Yi, Bo; Huang, Min (Neural computing & applications, 2020)
Malicious and selfish behaviors represent a serious security threat against routing in mobile social networks (MSN). Due to MSN’s unique network characteristics, such as sociability, mobility and diversity, it is a challenge to design a misbehavior detection scheme in MSN. To improve the security in MSN routing, a trust-based security routing mechanism is presented in this paper, i.e., a malicious behavior detection mechanism with identity verification scheme. The main idea is to introduce the behavior trust and the identity trust to guide the routing. Firstly, we judge a node’s behavior based on both comprehensive trust and social relationship strength. And then, we forward messages according to the different measurement within and outside the friend groups. We also propose a distributed key management scheme which can issue, verify or revoke certificates based on the evaluation of the social relationship strength. We further improve the efficiency of the proposed mechanism by verifying the identity trust of the node. The simulation results indicate that the proposed routing mechanism can lower the impact of malicious behavior of nodes effectively and it has greater security performance than some classical routing algorithms do.